Imperative Speech in Learning Process at TK Badak Mekar, Muara Badak, Kutai Kartanegara: A Pragmatic Analysis - Yusak Hudiyono; Suhana Suhana (CAKRAWALA LINGUISTA, 2018)
This study aims to describe the speech of kindergarten teachers Badak Mekar, Muara Badak, Kutai Kartanegara covering (1) imperative form, (2) imperative politeness. Data analysis used conversational analysis with pragmatic analysis technique. The validity of the data is obtained through observational persistence and triangulation is done during the teaching process. Data collection is done by tapping technique (participant observation), recording techniques, and collect as many as 124 imperative speeches. The results of the first study (1), the imperative form in the speech of the kindergarten of the Badak Mekar kindergarten include (a) the most commonly found structural form is the non-transitive active and passive imperative and (b) the most commonly found pragmatic form is the imperative form (command construction). (2) Secondly, the imperative courtesy of the teacher's speech includes (a) the most commonly found linguistic politeness is a gentle word, a low tone of speech, and polite kinesics gestures, and (b) the most common pragmatic pronunciation is maxima consensus and there is also a combination of two to three maxims. Pragmatic pronunciation based on the most commonly found speech constructions is declarative and interrogative construction.